Strain-modulated electronic transport in two-dimensional carbon allotropes - Ningjing Yang; Qingyuan Chen; Yafang Xu; Jinlong Luo; Hai Yang; Guojun Jin (AIP Advances, 2022)
Carbon has various allotropes showing rich physical properties. Here, we take net C and net W as the research objects. They are all composed of carbonic squares C4, hexagons C6, and octagons C8, but with different compositions. Using the combination of density functional theory calculations and non-equilibrium Green’s function method, we study the significant changes in electronic structures and transport behaviors in response to external strain. For net C, tunable negative differential resistance (NDR) is observed. The NDR bias region can be moved and widened, while its peak-to-valley ratio can be increased from the original 1.14 to largest 2.67. The electrical conductivity of net W exhibits a very good linear relationship within a large strain range from −4% to +4%, and it can be increased to 219.9%. By analyzing their band structures, the effective regulations of strain on both the NDR and linear conductivity are explained. These results show not only the differences from deformation for various carbon rings under strain but also a certain guiding significance for applications in electronic devices.